Henry Dumont and Nina Webster Dumont papers - Dumont, Henry, 1878-1942.; Dumont, Nina Webster, 1887-1953.
Henry Dumont's papers consist of correspondence (much of it with the poet George Sterling), printed matter, scrapbooks, clippings, business papers, and drafts of his biography of Sterling. Includes Dumont's correspondence about Sterling with Albert M. Bender, Theodore Dreiser, Arnold Genthe, Charmian London, Virgil Markham, William McDevitt, H. L. Mencken, George Steele Seymour, Upton Sinclair, and Sterling's daughters, Alice Chrystal Sterling Gregory and Mary Isabelle Sterling Routhwaite. Also includes poems by Sterling, many of them autographed. Also includes material on Dumont's career with Pacific Coast Borax Company and his involvement with the Business Men's Art Clubs of Chicago, New York, and San Francisco. Nina Webster Dumont's papers relate primarily to her work as statistician and conductor of surveys for the U.S. Bureau of Labor Statistics and other federal and state agencies on such topics as air pollution, consumer purchases, cost of living, health, medical care costs, and occupational morbidity and mortality.
Businessman, author, and poet. Married Nina Webster, statistician for the U.S. Bureau of Labor Statistics and other federal and state agencies.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bender, Albert M. -- 1866-1941 -- Correspondence; Dreiser, Theodore, -- 1871-1945 -- Correspondence; Genthe, Arnold, -- 1869-1942 -- Correspondence; Gregory, Alice Chrystal Sterling -- Correspondence; London, Charmian -- Correspondence; Markham, Virgil, -- 1899- -- Correspondence; McDevitt, William -- Correspondence; Mencken, H. L. -- 1880-1956 -- Correspondence; Routhwaite, Mary Isabelle Sterling -- Correspondence; Seymour, George Steele -- Correspondence; Sinclair, Upton, -- 1878-1968 -- Correspondence; Sterling, George, -- 1869-1926.; Sterling, George, -- 1869-1926 -- Correspondence; Business Men's Art Club of Chicago; Business Men's Art Club of New York; Business Men's Art Club of San Francisco; Pacific Coast Borax Company; United States. -- Bureau of Labor Statistics; Air -- Pollution -- Statistics; Cost and standard of living -- Statistics; Diseases -- Statistics; Medical statistics; Medical care, Cost of -- Statistics; Occupational mortality -- Statistics; Purchasing power -- Statistics; Authors; Businessmen; Poets; Statisticians